2012
DOI: 10.1371/journal.pone.0046955
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Screening for Down Syndrome Using Serum Placental Growth Factor with the Combined, Quadruple, Serum Integrated and Integrated Tests

Abstract: ObjectiveTo estimate the value of first or second trimester placental growth factor (PlGF) as an additional antenatal screening marker for Down syndrome.DesignNested case-control study.SettingAntenatal screening service.Population or Sample532 Down syndrome pregnancies and 1,155 matched unaffected pregnancies.MethodsStored maternal serum samples (−40°C) were assayed for PlGF. Monte Carlo simulation was used to estimate the screening performance of PlGF with the Combined, Quadruple, serum Integrated and Integra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 19 publications
2
18
0
Order By: Relevance
“…The consensus found in these recent studies is nearly identical to the median of 0.79 MoM in 243 cases reported in a 1999 meta‐analysis . A review of PlGF and Down syndrome in the first trimester identified nine published studies . One set of results was identified as an outlier, with the lowest median MoM (0.610) reported along with the highest z‐score (1.72).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The consensus found in these recent studies is nearly identical to the median of 0.79 MoM in 243 cases reported in a 1999 meta‐analysis . A review of PlGF and Down syndrome in the first trimester identified nine published studies . One set of results was identified as an outlier, with the lowest median MoM (0.610) reported along with the highest z‐score (1.72).…”
Section: Discussionmentioning
confidence: 54%
“…Important implementation considerations include what screening cut‐off should be used and how samples should be collected. Optimally, maternal plasma samples should be collected from all women at the time of first trimester serum screening, and the reflexive testing performed without informing each woman or the primary care provider of the preliminary results . In such a scenario, the proportion of initial tests considered positive would be mainly a function of the available funds for cf DNA testing.…”
Section: Discussionmentioning
confidence: 99%
“…Wald et al . predicted a 1–7% increase in detection rate depending on the week of gestation and false‐positive rate . Donalson rate et al .…”
Section: Discussionmentioning
confidence: 98%
“…Abnormal angiogenesis has also been related to other obstetric and fetal conditions such as peripartum cardiomyopathy and fetal cardiac defects, opening up new challenges for our understanding of angiogenic involvement in maternal cardiovascular function and fetal cardiac development [25]. Reduced maternal serum PlGF at 11-13 weeks has been reported in pregnancies that subsequently develop preeclampsia and intrauterine growth restriction [26,][27] and in those with fetal trisomy 21 [28,29]. In the case of preeclampsia, the low PlGF is accompanied by a low PAPP-A and a high uterine artery pulsatility index, and these findings are attributed to impaired trophoblastic invasion of the maternal spiral arteries, leading to reduced placental perfusion and function.…”
Section: Discussionmentioning
confidence: 99%